Post-Uthmanic Qur’anic Re-Canonization: A Historical Reconstruction of the Second Maṣāḥif Project during the Abbasid–Mamluk Era - Muchammad Fariz Maulana Akbar; Dody S. Truna; Rifki Rosyad (Parahyangan Catholic University, 2025)
This study aims to reconstruct the historical, philological, and ideological dynamics behind the phenomenon of post-Uthmanic Qur’anic re-canonization, known as the second maṣāḥif project. Specifically, it investigates how this process of textual reconsolidation unfolded during the Abbasid and Mamluk periods by highlighting the roles of scholars (ʿulamāʾ), political institutions, and bureaucratic mechanisms in shaping Sunni orthodoxy through the standardization of Qur’anic recitations (qirāʾāt). The study employs a qualitative-descriptive method with a historical-philological and sociological-ideological approach, based on an examination of classical maṣāḥif manuscripts (al-Dānī, Ibn Mujāhid, al-Suyūṭī) as well as secondary analyses from contemporary studies on the history of Qur’anic canonization. The findings reveal that the second maṣāḥif project represents a phase of textual and ideological consolidation marking the transition from oral to institutional authority. Ibn Mujāhid (d. 324 H/936 CE) played a central role in establishing the qirāʾāt sabʿah as the official boundary of canonical readings, supported by Abbasid political power to stabilize religious discourse and strengthen Sunni orthodoxy. The standardization of rasm Uthmānī and the elimination of non-canonical readings produced a hierarchical system of knowledge transmission, in which the qurrāʾ and ʿulamāʾ served as the exclusive mediators between the text and the Muslim community. Although this process achieved theological uniformity and ritual unity, it also resulted in dysfunctions—particularly the loss of linguistic and hermeneutical diversity within the qirāʾāt tradition. Theoretically, this study introduces the concepts of dual canonization and textual statecraft to explain the reciprocal relationship between sacred text, political authority, and the production of orthodoxy in classical Islam.